Echocardiographic assessment of left ventricular remodeling in American style footballers - Moneghetti, K. J.; Singh, T.; Hedman, K.; Christle,. W.; Kooreman, Z.; Kobayashi, Y.; Bouajila, S.; Amsallem, M.; Wheeler, M.; La Gerche, A.; Ashley, E.; Haddad, F. (International Journal of Sports Medicine, 2020)
Several athletic programs incorporate echocardiography during pre-participation screening of American Style Football (ASF) players with great variability in reported echocardiographic values. Pre-participation screening was performed in National Collegiate Athletic Association Division I ASF players from 2008 to 2016 at the Division of Sports Cardiology. The echocardiographic protocol focused on left ventricular (LV) mass, mass-to-volume ratio, sphericity, ejection fraction, and longitudinal Lagrangian strain. LV mass was calculated using the area-length method in end-diastole and end-systole. A total of two hundred and thirty players were included (18±1 years, 57% were Caucasian, body mass index 29±4 kg/m2) after four players (2%) were excluded for pathological findings. Although there was no difference in indexed LV mass by race (Caucasian 78±11 vs. African American 81±10 g/m2, p=0.089) or sphericity (Caucasian 1.81±0.13 vs. African American 1.78±0.14, p=0.130), the mass-to-volume ratio was higher in African Americans (0.91±0.09 vs. 0.83±0.08, p<0.001). No race-specific differences were noted in LV longitudinal Lagrangian strain. Player position appeared to have a limited role in defining LV remodeling. In conclusion, significant echocardiographic differences were observed in mass-to-volume ratio between African American and Caucasian players. These demographics should be considered as part of pre-participation screening.